Rekrutmen Politik dalam Proses Penentuan Keputusan Pencalonan Anis Baswedan – Sandiaga Uno di Partai Gerindra dan Partai Keadilan Sejahtera (PKS) dalam Pilgub DKI Jakarta Tahun 2017 - Rofiqi, Rofiqi (Global and Policy Journal of International Relations, 2019)
This research is drawn upon Anies Baswedan candidacy for Jakarta gubernatorial election which was supported by Gerinda and PKS even though he was a Jokowi proponent back in the 2014 presidential election. Despite the contradiction, Anies Baswedan was still appointed in the Jakarta gubernatorial candidacy. This research will be focusing on how the process of political recruitment behind Anies Baswedan- Sandiaga Uno’s appointment was conducted. Using political recruitment theory by Rush and Althoff, and elite theory by Nazaruddin Syamsuddin and Mosca, this research argues that their candidacy was done enclosed. Which mean, they did not get to deal with an internal selection of Gerinda, nor the wide selection (pemira) by PKS. Therefore, this research suggests that the Anies-Sandi gubernatorial candidacy was arranged by the elite trio: Jusuf Kalla, Prabowo Subianto and Shohibul Iman. Keywords: Anies Baswedan, Sandiaga Uno, Political Elite, Jakarta Gubernatorial Election 2017 DOi : https://doi.org/10.33005/jgp.v7i01.1818